2007
DOI: 10.5713/ajas.2007.742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-term Heat Exposure on Adaptive Mechanism of Blood Acid-base in Buffalo Calves

Abstract: In order to investigate the mechanism of adaptation to long-term heat stress, six female buffalo calves of about 7 to 8 months age, were exposed to the cool-comfort environment (THI 65) for 21 days to obtain normal values of blood acid-base. An adaptive response of acid-base regulation was determined to long term (21 days) exposure of buffalo calves to hot-dry (THI 80) and hothumid (THI 84) conditions. Higher rectal temperature and respiratory rate was recorded under hot-humid exposure compared to hot-dry. Sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 15 publications
(12 reference statements)
1
5
0
Order By: Relevance
“…The significant rise in RT during HS (37.54°C vs. 38.01, 38.77°C) indicate increasing heat load on the buffaloes and inability to normally dissipate the accumulating heat, consequently raising the body temperature. Significant increase in RT (p<0.001) was also seen in heat-exposed buffalo calves as compared to cool comfortable conditions [11]. Similarly, higher RTs (°C) were also seen in heat-exposed Tharparkar (38.74±0.11 vs. 38.96±0.05) and Karan Fries heifers (38.84±0.06 vs. 39.19±0.24) than at thermoneutral treatments validating our findings [12].…”
Section: Discussionsupporting
confidence: 84%
“…The significant rise in RT during HS (37.54°C vs. 38.01, 38.77°C) indicate increasing heat load on the buffaloes and inability to normally dissipate the accumulating heat, consequently raising the body temperature. Significant increase in RT (p<0.001) was also seen in heat-exposed buffalo calves as compared to cool comfortable conditions [11]. Similarly, higher RTs (°C) were also seen in heat-exposed Tharparkar (38.74±0.11 vs. 38.96±0.05) and Karan Fries heifers (38.84±0.06 vs. 39.19±0.24) than at thermoneutral treatments validating our findings [12].…”
Section: Discussionsupporting
confidence: 84%
“…A negative correlation between plasma protein and elevated environmental temperature has been reported in some studies (Habeeb 1987;Sejian et al 2008a). The biological significance of thermal-stress reducing proteins is to support hepatic gluconeogenesis by glucocorticoids to increase glucose levels to allow the animal to cope with thermal stress (Kamiya et al 2006;Korde et al 2007). The decrease in plasma protein may be due to dilution of plasma proteins and the decrease in protein synthesis as a result of depression of anabolic hormone secretion (El-Masry and Habeeb 1989).…”
Section: Discussionmentioning
confidence: 93%
“…The probable reason of reduction in BE might be due to low oxygen tension (PO 2 ) which might have increased anaerobic glycolysis to cause excess production of lactic acid. Korde et al [39] also reported low BE in buffalo calves in heat stress condition and suggested that it might be a compensatory response to respiratory alkalosis. West et al [40] also observed low BE in heat-stressed dairy cows and suggested that the reduction in BE might be due to either increased respiratory rate/panting under heat stress, which eliminated CO 2 in excess and caused decreased PCO 2 as well as carbonic acid, or it might be due to decrease in the non-bicarbonate buffer system, particularly Hb which resulted in decreased levels of buffer in blood.…”
Section: Bementioning
confidence: 99%